2015
DOI: 10.1038/sj.bdj.2015.889
|View full text |Cite
|
Sign up to set email alerts
|

Explaining diet as a risk factor for periodontal disease in primary dental care

Abstract: Using the entire dental team can be an effective way of educating our patients on risk factors for periodontal disease. It is important to note that this audit focused on clinicians delivering the advice and future direction should consider patient compliance and uptake of information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Although reports on oral health education in dental clinics are very scarce, the findings disclosed in our survey somehow agree with the reported low frequencies of adult patient recall of oral health education services received in private practice settings (McConaughy, Toevs, & Lukken, ). Although health education during dental visits is usually limited by time and frequently addressed to a particular problem (Raidi et al, ), systematic and organised efforts in combination with adequate information have proved useful in improving compliance with supportive periodontal therapy in dental clinics (Demirel & Efeodlu, ; Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although reports on oral health education in dental clinics are very scarce, the findings disclosed in our survey somehow agree with the reported low frequencies of adult patient recall of oral health education services received in private practice settings (McConaughy, Toevs, & Lukken, ). Although health education during dental visits is usually limited by time and frequently addressed to a particular problem (Raidi et al, ), systematic and organised efforts in combination with adequate information have proved useful in improving compliance with supportive periodontal therapy in dental clinics (Demirel & Efeodlu, ; Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind the reported low level of knowledge of periodontal health elicited by laypersons (Varela‐Centelles et al, ), together with the gaps observed for physicians and nurses (Varela‐Centelles et al, ), and combined with the high prevalence of periodontal disorders (Albandar & Rams, ), dental clinics should be expected to be the cornerstone of patient periodontal education. A pilot study on general dental practitioners found they perceived useful the participation of the entire dental team in educating patients on periodontal risk factors (Raidi, Thornley, & Thornley, ). In fact, much of the burden of patient education lies with dental hygienists because of their positive influence on patients’ knowledge, motivation and self‐care (Ultembroek, Schaub, Tromp, & Kant, ), and also because dentists find important barriers for educating their patients, such as lack of time, remuneration or patient compliance (Thevissen, Bruyn, & Koole, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the study by Sarmadi et al [94] also found that diet counselling was provided to ~10-20% of children and adolescents whereas diet information was provided to ~40-50% of children and adolescents attending public dental services in Sweden. In addition, Raindi et al [96] found in a small pilot study that diet advice was not provided for periodontal prevention. As well, an observation study [98,99] conducted in general dental practices in the United States found that overall <~10% of visits had nutrition counselling with the median number of 30 s intervals devoted to nutrition counselling being 0 (range: 0-6 for dentists; 0-23 for dental hygienists).…”
Section: General/unspecific Nutrition Intervention Practicesmentioning
confidence: 99%